Opposite Effects of Two Human ATG10 Isoforms on Replication of a HCV Sub-genomic Replicon Are Mediated via Regulating Autophagy Flux in Zebrafish - Li, Yu-Chen; Zhang, Miao-Qing; Zhang, Jing-Pu (Frontiers in Cellular and Infection Microbiology, 2018)
Autophagy is a host mechanism for cellular homeostatic control. Intracellular stresses are symptoms of, and responses to, dysregulation of the physiological environment of the cell. Alternative gene transcription splicing is a mechanism potentially used by a host to respond to physiological or pathological challenges. Here, we aimed to confirm opposite effects of two isoforms of the human autophagy-related protein ATG10 on an HCV subgenomic replicon in zebrafish. A liver-specific HCV subreplicon model was established and exhibited several changes in gene expression typically induced by HCV infection, including overexpression of several HCV-dependent genes (argsyn, leugpcr, rasgbd and scaf-2), as well as overexpression of several ER stress related genes (atf4, chop, atf6 and bip). Autophagy flux was blocked in the HCV model. Our results indicated that the replication of the HCV subreplicon was suppressed via a decrease in autophagosome formation caused by the autophagy inhibitor 3MA, but enhanced via dysfunction in the lysosomal degradation caused by another autophagy inhibitor CQ. Human ATG10, a canonical isoform in autophagy, facilitated the amplification of the HCV-subgenomic replicon via promoting autophagosome formation. ATG10S, a non-canonical short isoform of the ATG10 protein, promoted autophagy flux, leading to lysosomal degradation of the HCV-subgenomic replicon. Human ATG10S may therefore inhibit HCV replication, and may be an appropriate target for future antiviral drug screening.